Mapping urban spaces designing the European city - Amistadi, Lamberto 1972-; Balducci, Valter; Bradecki, Tomasz 1979-; Prandi, Enrico 1969-; Schröder, Uwe 1964- (Routledge, Taylor & Francis Group, 2022)
"Mapping Urban Spaces focuses on medium-sized European cities, and more specifically on their open spaces from a psychological, sociological and aesthetic point of view. The chapters illustrate how the characteristics that make life in medium-sized European cities pleasant and sustainable-accessibility, ease of travel, urban sustainability, social inclusiveness-can be traced back to the nature of that space. The chapters develop from a phenomenological study of space to contributions on places and landscapes in the city. Centralities and their meaning are studied as well as the social space and its complexity. The contributions focus on history and theory as well as concrete research and mapping approaches and resulting design applications. The case studies come from countries around Europe including Poland, Italy, Greece, Germany, and France, among others. The book will be of interest to students, scholars, and practitioners in architecture, urban planning, and landscape architecture"--
Includes bibliographical references and index
Keywords: Stadtplanung; Städtebau; Europa; City planning / Europe; Open spaces / Europe; Architecture and society / Europe; Aufsatzsammlung